Cadaveric study of branching pattern of left coronary artery - M Sobana; P S Chitra (Wolters Kluwer Medknow Publications, 2016)
Background and aim: The branching pattern of vascular system has been the subject of much discussion and debate since it was first suggested that these systems have fractal architecture. Coronary arteries of human heart and their branching pattern have been the subject of particular attention among researchers. Hence, this study of branching pattern of left coronary artery (LCA) has been undertaken to highlight the variations of branches of left coronary arterial system. Material and methods: The study material consisted of 50 heart specimens obtained from the cadavers of Anatomy and Forensic departments which were studied by the conventional dissection method. Results: Left posterior aortic sinus gave origin to left coronary artery in all specimens with 90% ostium being below the level of sinotubular junction (STJ). Nearly 50% specimens were of the length ranging between 6-10mm.Left coronary artery bifurcated into its two main branches in 62%, trifurcated in 32% and quadfurcated in 6%. Among the 16 trifurcating specimens, in five specimens the diagonal artery was seen at the junction of its two main branches, in 11 specimens the diagonal artery was found arising from the anterior interventricular artery and an additional branch the "Median Artery" was seen at the junction. Conclusion: Recent technical advances in the study of coronary arteries make it necessary for all angiographers and cardiac surgeons to be familiar with the variants of left coronary artery branching pattern.